Contribution of Extracellular Signal-Regulated Kinase to UTP-Induced Interleukin-6 Biosynthesis in HaCaT Keratinocytes - Daisaku Kobayashi; Satoko Ohkubo; Norimichi Nakahata (Elsevier, 2006)
UTP causes interleukin (IL)-6 production via mRNA expression through P2Y2/P2Y4 receptors in human HaCaT keratinocytes. In the present study, we analyzed the mechanism of UTP-induced IL-6 production in these cells. UTP, an agonist of P2Y2/P2Y4 receptors, induced phosphorylation of extracellular signal-regulated kinase (ERK) in a concentration- and time-dependent manner. PD98059, a MEK (mitogen-activated protein kinase kinase) inhibitor, and BAPTA-AM [O,O'-bis(2-aminophenyl)ethyleneglycol-N,N,N',N'-tetraacetic acid, tetraacetoxymethyl ester], an intracellular Ca2+ chelator, reduced UTP-induced ERK phosphorylation and IL-6 mRNA expression. 2-APB [(2-aminoethoxy)diphenylborane], an inositol 1,4,5-trisphosphate (IP3)-receptor antagonist, inhibited UTP-induced IL-6 mRNA expression; and the action of A23187, a Ca2+ ionophore, resembled the action of UTP. In contrast, protein kinase C (PKC) downregulation and pertussis toxin did not affect UTP-induced IL-6 mRNA expression, suggesting that PKC and Gi are not involved in the UTP-induced IL-6 production. However, AG1478, an epidermal growth factor (EGF)-receptor inhibitor, partially decreased UTP-induced ERK phosphorylation and IL-6 expression. These results suggest that UTP-induced IL-6 production is in part mediated via phosphorylation of ERK through Gq/11/IP3/[Ca2+]i and transactivation of the EGF receptor. Keywords:: interleukin-6, extracellular signal-regulated kinase (ERK), HaCaT, Ca2+ elevation, epidermal growth factor (EGF) receptor